Aplikasi Pendaftaran Pasien Berbasis Android pada Apotek Cordelia Tanjungpinang - Rio Ari Prasetio; Ira Purnamasari; Nanny Raras Setyoningrum (Jurnal Bangkit Indonesia, 2018)
Cell phones are a phenomenon of the most interest since the end of the last century. A phenomenon that began in the 1990s and develops until now. Cellular phones now have an Operating System that is able to manage and control all applications, there are various operating systems such as Symbian, Windows Mobile, Palm, Blackberry and Android which are new today. Thus the authors are interested in creating an android application that makes it easy for people to seek treatment at a health clinic. The system created is a system that makes it easier for people to see the queue number so that people who are going for treatment do not have to wait too long at the clinic. In designing this class the research methodology used is data collection. The data collection method consisted of literature study and experiment. Android-Based Patient Registration Application at Cordelia Pharmacy and General Practitioner Practices Jl. RE. Martadinata Tanjungpinang is implemented based on a needs analysis using Android applications, PHP and Java programming languages, PHP MySql as a database.